Structure-based insights into self-cleavage by a four-way junctional twister-sister ribozyme. Issue 1 (December 2017) - Zheng, Luqian; Mairhofer, Elisabeth; Teplova, Marianna; Zhang, Ye; Ma, Jinbiao; Patel, Dinshaw; Micura, Ronald; Ren, Aiming
Abstract Here we report on the crystal structure and cleavage assays of a four-way junctional twister-sister self-cleaving ribozyme. Notably, 11 conserved spatially separated loop nucleotides are brought into close proximity at the ribozyme core through long-range interactions mediated by hydrated Mg2+ cations. The C62–A63 step at the cleavage site adopts a splayed-apart orientation, with flexible C62 directed outwards, whereas A63 is directed inwards and anchored by stacking and hydrogen-bonding interactions. Structure-guided studies of key base, sugar, and phosphate mutations in the twister-sister ribozyme, suggest contributions to the cleavage chemistry from interactions between a guanine at the active site and the non-bridging oxygen of the scissile phosphate, a feature found previously also for the related twister ribozyme. Our four-way junctional pre-catalytic structure differs significantly in the alignment at the cleavage step (splayed-apart vs. base-stacked) and surrounding residues and hydrated Mg2+ ions relative to a reported three-way junctional pre-catalytic structure of the twister-sister ribozyme. Twister-sister is a self-cleaving ribozyme. Here, the authors report the 2.0 Å crystal structure of the four-way junctional twister-sister ribozyme in the pre-catalytic state and discuss mechanistic implications based on their mutagenesis experiments and comparisons with other ribozyme structures.